Influenza Immunization Data: Can We Make Order Out of Chaos? - Jennifer A. Pereira, Christine L. Heidebrecht, Susan Quach, Sherman D. Quan, Michael Finkelstein, Julie A. Bettinger, Shelley L. Deeks, Maryse Guay, David L. Buckeridge, Larry Chambers, Natasha S. Crowcroft, Beate Sander, Donna Kalailieff, Stephanie Brien and Jeffrey C. Kwong (Healthcare Quarterly, 2011)
The 2009 H1N1 pandemic vaccination campaign was an excellent opportunity to witness the many benefits of collecting individual-level immunization data at the point of vaccination. Most provinces and territories required the reporting of at least partial demographic vaccination data from their local public health agencies, so timely vaccine coverage data were available to inform operational planning and infection prevention activities.
Keywords: Influenza Immunization H1N1 Vaccination